Pre-/Post-traumatic Stress Symptoms of Qanun Defendants: A Case Report - Dian, Cut N.; Efffendy, Elmeida; Amin, Mustafa M. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Caning sentence has been applied for over a decade which is performed publicly. Given that emotional features of the defendants of the caning sentence occur, psychological symptoms may have emerged. One of the executions for the defendants is whipping practice that resembles military punishment, in which the penalty could have affected their personality pre and post-execution. CASE REPORT: In this report, a 30-year-old married woman was sentenced to Qanun criminal offense in Aceh due to her despicable relationship to a male individual who is also a husband of someone. As the caning regulation stated that the punishment execution must be performed through whipping in public places, the women demonstrated several mental conditions such as anxiety, sleeping disorders, and unmotivated in the last 3 days before execution. CONCLUSION: Caning practice in Aceh is performed by following the guidance from a medical doctor to prevent unexpected physical damage; however, psychological symptoms that could last for several years in the future might have occurred. Thus, a high prevalence of mental disorders has appeared among the defendants.